Building Emotional Awareness and Mental Health (BEAM): A Pilot Randomized Controlled Trial of an App-Based Program for Mothers of Toddlers - MacKinnon, Anna L.; Simpson, Kaeley M.; Salisbury, Marlee R.; Bobula, Janelle; Penner-Goeke, Lara; Berard, Lindsay; Rioux, Charlie; Giesbrecht, Gerald F.; Giuliano, Ryan; Lebel, Catherine; Protudjer, Jennifer L. P.; Reynolds, Kristin; et al. (Frontiers in Psychiatry, 2022)
Families have faced unprecedented challenges during the COVID-19 pandemic, leading to increased maternal mental health problems and barriers to accessing care. Innovative programs are needed to support both maternal mental health and parenting, and to buffer the long-term impacts of stress on young children. Using a patient-oriented approach, our research team co-developed and pilot tested an App-based psychoeducation and social-connection platform: Building Emotional Awareness and Mental Health (BEAM). The co-development process involved a parent advisory board from conceptualization and design, through to direct participation in the program delivery. The BEAM program includes weekly videos and activities based on Unified Protocol therapy modules and emotion-focused parenting strategies, a weekly telehealth group review session, and access to a private online forum for support from other mothers and clinical coaches. A pilot randomized control trial was conducted across two provinces in Canada. 65 mothers of preschool children (aged 18-36 months old), with moderate-to-severe depression (Patient Health Questionaire-9≥10), were allocated to either the 10-week BEAM intervention (n=33) or treatment as usual control (n=32) groups. Participants completed questions about feasibility and acceptability of the program and pre/post self-report measures of mental health, parenting, positive coping and child behavior outcomes. Engagement was relatively high at the beginning of the program, with 78.8% starting the BEAM App and 70.6% attending ≥1 telehealth session. Most respondents felt socially supported, satisfied with the App, and found it easy to use. Data were analysed using mixed models and an intention-to-treat approach. Pre-post results indicated interaction effects with greater reductions in overall mental health problems and specific anxiety and sleep symptoms among BEAM versus control participants, as well as time effects with reductions in depression symptoms across both groups. No significant treatment effects emerged for the other mental health symptoms, parenting problems, positive coping, or child behaviour outcomes. Descriptive data are included to highlight possible areas of promise for future large efficacy trials. Technological difficulties and other challenges that may have led to attrition and impacted outcomes are discussed. The BEAM program has promise as a novel, feasible and acceptable intervention for improving mental health among mothers of young children.